Analysis of Factors Causing Delays in Elective Surgery in Central Hospital Surgical Installations - B, Sari Arie Lestari; Kartika, Ade; Madani, Ultra; Ohorella, Usman Barus; Harlina, Harlina; Aryadi, Anggi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Overcrowding in the emergency department is defined as a situation where the emergency department has more patients than treatment rooms or more patients than the staff should ideally handle, and the emergency department is an overcrowded place, with patient volumes far from capacity. and forcing emergency departments to operate beyond their capacity. Delays in elective surgery are one of the National Quality Indicators which are closely related to perioperative services in Central Surgical Installations. The Central Surgery Installation is one of the installations that provides perioperative services in hospitals. This installation provides well-planned surgical services. The aim of the research is to determine the factors that cause delays in elective surgery in the Central Surgery Installation. Method This research uses a retrospective observational analytic method with a cross-sectional approach. The sampling technique used is cluster sampling which is taken randomly. The analysis used is Logistic Regression. Research Results There is a significant relationship between patient factors and staff factors. The conclusion is that staff factors are the most dominant factor influencing surgical delays in the Central Surgical Installation.